Molecular characterization and comparisons of potato wart (Synchytrium endobioticum) in historic collections to recent findings in Canada and the Netherlands - Vossenberg, B.V. de; Gent, M.V.; Meffert, J.P.; Nguyen, H.D.; Smith, D.; Kempen, T.V.; Helderman, C.M.; Rosendahl-Peters, K.C.; Braak, N.T.; Flath, K.; Przetakiewicz, J.; Pérez, W.; et al. (Springer, 2023)
Synchytrium endobioticum (Schilb.) Perc. is a chytrid fungus causing potato wart disease and is one of the most important quarantine diseases on cultivated potato. Infected host tissues develop warts rendering the crop unmarketable. Resting spores, that can remain viable and infectious for decades, are formed in warted tissues and are released into the surrounding soil when host tissue decays. To better understand the pathogen’s diversity and to potentially uncover pathways of migrations and introduction events, molecular characterization was performed on the historical S. endobioticum resting spore collection of the Dutch National Plant Protection Organization. Mitochondrial genomes were assembled and annotated, and four novel structural variants were identified from these materials with intronic presence-absence variation in cox1 or cob genes and structural variation in the dpoB – TIR region. Several fungal isolates were shown to contain mixtures of structural variants. We analyzed the mitogenomic sequences obtained from recent potato wart disease findings in Canada and the Netherlands in the context of the historical materials and found that fungal isolates from the new Dutch outbreak contained a specific mixture of mitogenomic variants previously not observed in the Netherlands. Based on the mitogenomic profile, pathotype 38(Nevşehir) was suspected which was later verified with the Spieckermann bioassay. To further facilitate dissemination of data and interactive visual analytics we created a public Nextstrain webpage with S. endobioticum mitogenomic sequences and associated metadata on their geographic origin, pathotype identity and (mixture) of mitogenomic variants (https://nextstrain.nrcnvwa.nl/Sendo).